Computer-aided re-engineering of nonribosomal peptide and polyketide biosynthetic assembly lines - Alanjary, Mohammad; Cano-Prieto, Carolina; Gross, Harald; Medema, Marnix H (Natural product reports, 2019)
Covering: 2014 to 2019 Nonribosomal peptide synthetases (NRPSs) and polyketide synthases (PKSs) have been the subject of engineering efforts for multiple decades. Their modular assembly line architecture potentially allows unlocking vast chemical space for biosynthesis. However, attempts thus far are often met with mixed success, due to limited molecular compatibility of the parts used for engineering. Now, new engineering strategies, increases in genomic data, and improved computational tools provide more opportunities for major progress. In this review we highlight some of the challenges and progressive strategies for the re-design of NRPSs & type I PKSs and survey useful computational tools and approaches to attain the ultimate goal of semi-automated and design-based engineering of novel peptide and polyketide products. This review highlights recent advancements in engineering biosynthetic assembly lines and new computational tools that aid in parts search, assembly line engineering, and refinement.